Endoscopic Management of Transmural Defects, Including Leaks, Perforations, and Fistulae - Bemelman, Willem A; Baron, Todd H (Gastroenterology (New York, N.Y. 1943), 2018)
Transmural defects of the gastrointestinal tract can be classified into 3 distinct entities-leak, perforation, and fistula. Each arises from different mechanisms and is managed accordingly. Leaks occur most often after surgery, while perforations occur most often after flexible endoscopic maneuvers. Fistulae arise from a variety of mechanisms, such as an evolution from surgical leaks, as well as from specific disease states. Endoscopic management plays a vital role in the treatment of transmural defects as long as the region of interest can be accessed with the appropriate endoscopic accessories. Endoscopic approaches can be broadly classified into those that provide closure and those that provide diversion of luminal contents. With advances in technology, a myriad of devices and accessories are available that allow a tailored approach. Endoscopic approaches to leaks, perforations, and fistulae are discussed in this review.Transmural defects of the gastrointestinal tract can be classified into 3 distinct entities-leak, perforation, and fistula. Each arises from different mechanisms and is managed accordingly. Leaks occur most often after surgery, while perforations occur most often after flexible endoscopic maneuvers. Fistulae arise from a variety of mechanisms, such as an evolution from surgical leaks, as well as from specific disease states. Endoscopic management plays a vital role in the treatment of transmural defects as long as the region of interest can be accessed with the appropriate endoscopic accessories. Endoscopic approaches can be broadly classified into those that provide closure and those that provide diversion of luminal contents. With advances in technology, a myriad of devices and accessories are available that allow a tailored approach. Endoscopic approaches to leaks, perforations, and fistulae are discussed in this review.